Power Command Optimal Allocation Model of Distributed Energy System Based on Improved Firefly Algorithm - Xue, Xiao; Zheng, Yangbing; Lu, Chao (Distributed Generation & Alternative Energy Journal, 2022)
In order to enhance the power command allocation effect of distributed energy system, the modified firefly algorithm is established to deal with the optimal model of the proposed power command allocation. Firstly, the basic function and physical structure of power grid system distributed energy sys- tem are analyzed. Secondly, theoretical model of power command allocation model distributed energy system is constructed. Thirdly, the improved firefly algorithm is established. Finally, a power grid system distributed energy system with eight units is selected to carry out simulation analysis, results illustrate that the model has quickest convergence efficiency, and can obtain optimal power command allocation effect distributed energy system.